Indonesia's budget 2022 : too ambitious? - Borsuk, Richard (2021)
On top of all the other damage it has done in Indonesia, COVID-19 has hurt tax collection. That’s a problem, as the country needs to collect more tax to help fund spending and reduce borrowing needs. Is the next budget too ambitious?